DETERMINATION OF PERCEPTION REGARDING THE “TEACHING PROFESSION” OF TEACHER CANDIDATES: A WORK OF METAPHOR ANALYSIS - Murat BAŞ; Gülay EKİCİ and Onur KIZILKAYA (International Journal of Eurasia Social Sciences, 2017)
The aim of this research is to determine metaphors developed by teacher candidates about the concept of teaching profession. In the research phenomenological method has been used in the scope of qualitative research method. Teacher candidates’ metaphors are determined via semi-structured form. In this form, teacher candidates asked to fill in the blanks of sentences such as “teaching profession is like.......”.Because......”. Content analysis technique has been used in data analysis process. In the research, teacher candidates have developed 50 metaphors at total about concept of “teaching profession”. Developed metaphors combined in 7 different categories. These categories ranked based on how much they contain metaphors; categories named such as "teaching profession in terms of formative characteristic, teaching profession in terms of value, teaching profession in terms of guiding feature, teaching profession in terms of sacrifice, teaching profession in terms of being a knowledge source, teaching profession in terms of teaching profession in terms of volunteering, teaching profession in terms of being a model". Even live metaphors with high frequency have been developed regarding the teaching profession; generally lifeless metaphors have been created. If we look at the other categories of teaching profession according to its being source of knowledge feature, teaching profession according to its being directive and model, teaching profession according to its voluntarism feature and teaching profession according to its devotion feature has been developed in order to highlight the profession’s required specialties. Although teacher candidates have been stated such positive image and perspective of teaching profession, if we look at the feature of t high value, it is evaluated as at low level, means that teaching profession has not been valued properly.